Narración sonora: estrategia para fortalecer la memoria colectiva y la identidad territorial. - Oliveros, Mónica Paola Díaz; Ballesteros, Wendy Juliana Ahumada; Castillo, Linda Tatiana Parra (Enunciación, 2026)
This paper presents the results of a research project that arose from a commitment to rescue, appropriate, preserve, and disseminate the collective memory of the population from Bojacá, a municipality in Cundinamarca, Colombia. It is one of the phases within a macro-project called Words of ancestral paths: A proposal from cultural memory for strengthening community tourism development in the municipality of Bojacá. Its methodology, based on a sociocritical paradigm, draws on the tools of qualitative approaches. The results of this phase fall under the categories of territory and collective memory; therefore, the reader will encounter a project that uses digital narratives in the form of podcasts as an alternative for the construction and dissemination of the stories of the territory, leading, among other conclusions, to an understanding about the importance of oral tradition in strengthening memory. This work mobilizes methodological tools specific to action research that amplify and drive the social appropriation of knowledge.